ANALYSIS DETERMINATION OF EMPLOYEE PRODUCTIVITY THROUGH COMPENSATION AND JOB SATISFACTION - Kusuma Wardhani, Nia; Anggraini, Riska (International Journal of Advanced Multidisciplinary, 2022)
Human resources are a parameter of resources that are needed in an organization, because human resources play an active role in an organization achieving its goals. Organizational productivity depends on the work productivity of the individuals themselves. This research was conducted with the aim of analyzing how influential compensation and job satisfaction are on the job productivity of employees of a telecommunication company. The population of this study is 75 employees and determined sample uses the Slovin formula with an error margin of 5%. Methods of data collection using survey methods, in which the research instrument is a questionnaire. This research is a quantitative research using data analysis techniques Structural Equation Model (SEM) and data processing using Partial Least Square (PLS). This research resulted in the conclusion that compensation has a positive and significant effect on work productivity, and job satisfaction also has a positive and significant effect on employee work productivity.